2021
DOI: 10.4103/eus-d-20-00203
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of EUS-guided tissue acquisition in children: A tertiary care center experience

Abstract: Background and Objectives: EUS is frequently utilized for tissue acquisition in adult patients. However, the literature is limited regarding the utility of EUS-guided fine-needle aspiration or biopsy (FNA or FNB) in children. In this study, we aim to evaluate the feasibility, safety, and diagnostic utility of EUS-FNA/FNB in children with various gastrointestinal diseases. Methods: The data of children (≤18 years) who underwent EUS-FNA/FNB from March 2014 to June 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The feasibility, safety, and diagnostic utility of EUS-guided tissue acquisition in pediatrics with different indications were reported by a large Indian study including 76 cases. 17 The main indications for EUS in this report were solid pancreatic tumors (43.3%) and lymphadenopathy (44.7%). The authors confirmed the successfulness of all procedures without major complications.…”
Section: Discussionmentioning
confidence: 56%
“…The feasibility, safety, and diagnostic utility of EUS-guided tissue acquisition in pediatrics with different indications were reported by a large Indian study including 76 cases. 17 The main indications for EUS in this report were solid pancreatic tumors (43.3%) and lymphadenopathy (44.7%). The authors confirmed the successfulness of all procedures without major complications.…”
Section: Discussionmentioning
confidence: 56%
“…The endoscopists were very experienced in the management of adult patients, enabling the procedure to be safe and efficient also in the pediatric patients, which corresponds well with other studies. 1 , 3 , 8 , 9 , 10 , 11 , 16 , 17 , 18 While EUS was shown previously as a safe diagnostic method in the pediatric population, covering the age range of our patients (age 8 and 9 years, respectively), there is limited experience with EUS especially in smaller children (< 15 kg) due to the fear of an esophageal rupture associated with the large diameter (adult) EUS scope. Therefore, for smaller children (< 15 kg) endobronchial ultrasound has been used instead and a few studies have shown that EUS can be performed safely and with a high diagnostic accuracy even in these children.…”
Section: Discussionmentioning
confidence: 94%
“…According to the reviewed literature ( Table 2 ), the adoption of EUS for children with pancreatobilliary diseases was delayed due to different reasons, among them the low incidence of tumorous lesions and even rarer malignancies. 8 Other important reasons were also the size limitation of EUS equipment relative to pediatric anatomy, the low number of skilled pediatric endoscopists with EUS expertise, the need for sedation or general anesthesia, and a limited awareness among pediatric practitioners of EUS diagnostic and therapeutic possibilities. 3 , 8 In our patients, the procedure and equipment used was similar to the adult population, apart from the use of general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 There is no absolute contraindication to EUS-guided tissue acquisition, but caution is required in cases of cardiopulmonary instability, bleeding tendency with coagulopathy or thrombocytopenia, and recent use of anticoagulants or antiplatelets. 67…”
Section: Rose Versus Mosementioning
confidence: 99%